Relationships between Circulating Matrix Metalloproteinases, Tissue Inhibitor TIMP-2, and Renal Function in Patients with Myocarditis - Małgorzata Kobusiak-Prokopowicz (Karger Publishers, 2021)
Introduction: Under physiological conditions, the myocardial extracellular matrix (ECM) is maintained by matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs). However, changes in the balance between MMPs and TIMPs can lead to pathological remodeling of the ECM, which contributes to cardiovascular and kidney diseases. The aim of our study was to assess levels of MMPs and TIMP-2 in patients with myocarditis and their relationship to renal function. Materials and Methods: Forty five patients with myocarditis who underwent CMR were included, comprising 11 with concurrent chronic kidney disease (CKD). Blood samples were obtained to assess serum levels of MMP-2, MMP-3, MMP-9, and TIMP-2. Results: Serum MMP-2, MMP-3, and TIMP-2 levels negatively correlated with the ejection fraction in patients with myocarditis, while MMP-3 levels correlated with longitudinal deformation (p < 0.05). Serum MMP-2, MMP-3, and TIMP-2 levels also negatively correlated with renal function, as assessed by the estimated glomerular filtration rate (eGFR) (p < 0.05). Patients with myocarditis and concurrent CKD had higher levels of MMP-2 and TIMP-2 than those without kidney damage. Conclusions: (1) We demonstrated that MMP-2, MMP-3, and TIMP-2 concentrations were related to left-ventricular ejection fraction, and MMP-3 levels correlated with longitudinal deformation, indicating MMPs play an important role in the post-inflammatory remodeling of the myocardium. (2) A negative correlation between the eGFR and MMP-2, MMP-3, and TIMP-2 and a positive correlation between creatinine and MMP-3 levels indicate the role of MMPs and TIMP-2 in renal dysfunction.